(3CKQ GSJNOGe GddYH aj JfejI GdJaGYd GdGLJeGYj hJage eYfi GdSdGe hJMSjf Sdhc JdGePI GdUa GdNGeS CSGSj JLGg GdBNQjf hJLGg GdeLJeYs - (3GdcQOj, fGOjfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2012)
(3JJfGhd gPg GdOQGSI GdYfa GdPj jYjTg GdJdGePI Ef cGf aj JhGUdge eY HYVge GdHYV Ch eY GdeMjW eeG jDOj Edi JOghQ GdYdGbGJ GdGLJeGYjI GdJj gj CSGS Jchjf GdTNUjI(B. (3hJgOa GdOQGSI Edi EjLGO GdMdhd deTcdI GdYfa hGdfRGYGJ GdJj jYGfj efgG GdJdGePI hGdJj JfYcS SdHG Ydi Sdhcge GdGLJeGYj hHGdJGdj JTcd YGFbG dge CeGe JYRjR GdYdGbGJ eY GdBNQjf hPdc ef NdGd hVY HQfGeL JONd dJUMjM h JYOjd gPg GdSdhcjGJ(B. (3dJMbjb gPG GdgOa GSJYed GdefgL GdJLQjHj YHQ GdedGMXI GdeHGTQI dJbUj GdSdhcjGJ ZjQ GdShjI dOi JdGePI GdUa GdNGeS CSGSj hGdebGHdGJ hebjGS egGQGJ GdSdGe dbjGS bOQI GdJdGePI Ydi GcJSGH GdegGQGJ GdJj JSGYOge Ydi Jbdjd GdYfa hGdeTGQcI GdEjLGHjI hGdJaGYd GdGLJeGYj hegGQGJ eSGYOI GdBNQjf hGdMhGQ GdEjLGHj(B. (3NdUJ GdOQGSI Edi CgejI EbGeI HQfGeL GdJONd GdPj jMed YfhGf(B"(3GddYH cYGed eDKQ Ydi Md GdfRGYGJ(B"(3, HgOa eSGYOI GdJdGePI Ydi GdJNdU ef eLehYI cHjQI ef GdSdhcjGJ GdSjFI hJYOjd Sdhc GdPjf jYGfhf ef JOfj eSJhi GdJYGWj eY GdBNQjf hEcSGHge egGQGJ GdSdGe GdJj JSGYOge Ydi HfGA TNUjJge ef LOjO HGdEVGaI Edi JYdjege cjajI Md GdfRGY HYjOG Yf GdYfa(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3GdSdhc GdGLJeGYjs; Comportement Social; Cycle moyen; Intermediate Education; Jouer et jeux; Play and games; Social Behavior; (3GddYH hGdGdYGHs; (3GdeQMdI GdeJhSWIs